Evaluation of Transit Oriented Development Implementation in Blok M BCA Station Area - Herika Muhamad Taki; Nayla Maqsyura; Elisabet Dame Sidabuatar (Universitas Trisakti, 2025)
Blok M area, located in Kebayoran Baru, South Jakarta, is one of the locations for the development of transit-oriented areas or Transit-Oriented Development (TOD). TOD development is carried out in areas that have added value by encouraging sustainable movement through increased use of public transportation. The development of the area also prioritizes facilities for non-motorized vehicles and pedestrians, integrated with transportation nodes. This research aims to evaluate the Blok M TOD area to assess the extent of its conformity to the criteria of the TOD concept. The results show that the level of conformity of the Blok M transit area is only 85.215%, meaning that the Blok M area has not yet reached TOD standards. To achieve a more ideal TOD, sustainable space management is needed, reducing dependence on private vehicles, and improving the quality of public spaces that are friendly to all levels of society.